Detection and Classification of Dibetic Retinopathy in Color Fundus Image - B. Kale, Priyanka; Janwe, Nitin (International Journal For Research In Advanced Computer Science And Engineering, 2017)
Diabetic Retinopathy (DR) is an eye syndrome due to diabetes which causes optical loss. So it is sensible to offer treatment for DR at primary stages of disease. Haemorrhages are the initial symptoms that indicate person have diabetic retinopathy. Therefore, their acknowledgment is very crucial. In this paper image contrast is enhanced by pre-processing and then blood vessels are detected as the margins of haemorrhages are not discriminate when they are in contact with blood vessels. then classified the image on the basis of quality characteristic such as area in three stages as normal, moderate or Severe DR. classified images are classified with 99% accuracy. we tested set of images and obtained Precision= 0.99974, Recall=1, F1Score=0.99987.our approach has potential to be used as too in clinic for haemorrhages detection.